Upaya Meningkatkan Hasil Belajar Siswa SD Negeri 1 Parapat Melalui Model Problem Based Learning (PBL) pada Pendidikan Agama Katolik - Rame Yuniati Simanjuntak (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
of Catholic Religious Education and Ethics aims to shape students into individuals who have faith, piety, and noble character. This research focuses on increasing the spiritual potential of students through the introduction and cultivation of religious values. However, the lecture method that has been used has resulted in low motivation and student learning outcomes. This research was conducted at SD Negeri 1 Parapat with the application of the Problem Based Learning (PBL) Model to improve student independence and learning outcomes. The research method used is Classroom Action Research (PTK) which is carried out in two cycles. The results of the pre-test showed that only 2 out of 6 students were complete. In the first cycle, there was an increase in the average score to 76.7 with classical completeness of 70%. In the second cycle, the average grade increases to 100%, with 100% of students achieving completion. This study concludes that the PBL method is effective in improving student learning outcomes, independence, and creativity. The advice for teachers is to apply the PBL method consistently, for students to actively seek learning resources, and for schools to recommend PBL methods in each subject. This research emphasizes the importance of further development in the application of PBL for religious education.